2010
DOI: 10.1111/j.1468-1331.2010.03311.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasu-Hakola disease with a splicing mutation of TREM2 in a Japanese family

Abstract: This is the first report of a Japanese NHD family caused by a splicing mutation of TREM2 that induces both neuroinflammation and neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 8 publications
2
49
0
Order By: Relevance
“…The R47H variant of Trem2 confers a 3-fold increase in risk for AD [132,133], comparable to the risk conferred by the apolipoprotein E4 allele. Trem2 mutations are responsible for Nasu-Hakola disease [136]. These findings suggest that Trem2 may play a fundamental role in disease etiology.…”
Section: Trem2/trem2 Ligandmentioning
confidence: 84%
“…The R47H variant of Trem2 confers a 3-fold increase in risk for AD [132,133], comparable to the risk conferred by the apolipoprotein E4 allele. Trem2 mutations are responsible for Nasu-Hakola disease [136]. These findings suggest that Trem2 may play a fundamental role in disease etiology.…”
Section: Trem2/trem2 Ligandmentioning
confidence: 84%
“…Demyelinated lesions of MS are often accompanied by perivascular infiltration of numerous T lymphocytes, while NHD brain lesions contain a limited number of CD3-positive T cells [19], supporting the general view that MS is a T cell-mediated autoimmune disease affecting the central nervous system white matter, whereas autoimmune mechanisms are unlikely to play a central role in the pathogenesis of NHD. Previously, we found that the levels of expression of a guanine nucleotide exchanger for Rap termed RAPGEF4, which plays a role in the inhibition of autophagy [34], are greatly reduced in NHD brains [35]. All of these observations suggest the hypothesis that aberrant regulation of autophagy might induce oligodendrogliopathy causative of leukoencephalopathy in NHD brains.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, autophagy itself controls inflammation through regulatory interactions with innate immune signaling pathways [40]. By gene expression profiling, we recently identified 324 DEGs expressed in frozen brain tissues of a NHD patient with a splicing mutation of TREM2 [35]. Among them, the set of 136 genes involved in inflammatory response and immune cell trafficking are upregulated, while the set of 188 genes including a battery of GABA receptor subunits and synaptic proteins are downregulated in NHD brains.…”
Section: Discussionmentioning
confidence: 99%
“…In adult mouse brain, NAV3 is expressed chiefly in nuclear membranes of neurons in the cerebral cortex, midbrain, cerebellum, and the hippocampal formation (Coy et al 2002). Although, the biological function of (Table 1) and h the set of 188 genes downregulated in the brain of a NHD patient (Numasawa et al 2011). The network g showed the most significant relationship with the network defined by ''cell-to-cell signaling and interaction, hematological system development and function, and inflammatory response'', while the network h exhibited the most significant relationship with the network defined by ''neurological disease, organismal injury, and abnormalities, and behavior''.…”
Section: (F) Geneclipmentioning
confidence: 99%
“…In this network, the nuclear factor-kappa B (NF-jB) complex acts as a central regulator for the set of downregulated genes in DAP12 knockdown cells. Recently, by microarray analysis, we identified 188 downregulated genes, composed of various GABA receptor subunits and synaptic components, in the brain of a NHD patient with a splicing mutation of TREM2 (Numasawa et al 2011). Although, there exists no overlap between the set of 188 genes downregulated in the NHD brain and the set of 22 genes downregulated in DAP12 knockdown THP-1 cells, the molecular network of 188 genes showed the most significant relationship with the network defined by ''neurological disease, organismal injury and abnormalities, and behavior'' (P = 1 9 10E-66), where NF-jB again acts as a key regulator (Fig.…”
Section: Gene Expression Profile Of Dap12 Knockdown Thp-1 Clonesmentioning
confidence: 99%